Mark Alexandrovich Krasnosel'skii, (April 27, 1920 - February 13, 1997). (1997) - Asarin, E. A.; Bakhtin, I. A.; Bobylev, N. A.; Bondarenko, V. A.; Burd, V. Sh.; Chernorutskii, V. V.; Gorin, E. A.; Kozyakin, V. S.; Krasnosel'skii, A. M.; Kurzhanskii, A. B.; Kuznetsov, N. A.; Levin, A. Yu.; et al.
Abstract : On February 13, 1997, the world famous mathematician, Mark Alexandrovich Krasnosel'skii, died unexpectedly. This article gives a brief overview of his life and research.